Extracellular vesicles and its advances in female reproduction - de ávila, Ana Clara Faquineli Cavalcante Mendes; Andrade, Gabriella Mamede; Bridi, Alessandra; Gimenes, Lindsay Unno [UNESP]; Meirelles, Flávio Vieira; Perecin, Felipe; da Silveira, Juliano Coelho (Colegio Brasileiro de Reproducao Animal - CBRA, 2018)
Intercellular communication is an essential mechanism for development and maintenance of multicellular organisms. Extracellular vesicles (EVs) were recently described as new players in the intercellular communication. EVs are double-membrane vesicles secreted by cells and are classified according to their biosynthesis, protein markers and morphology. These extracellular vesicles contain bioactive materials such as miRNA, mRNA, protein and lipids. These characteristics permit their involvement in different biological processes. Reproductive physiology is complex and involves constant communication between cells. Different laboratories have described the presence of EVs secreted by ovarian follicular cells, oviductal cells, in vitro produced embryos and by the endometrium, suggesting that EVs are involved in the development of gametes and embryos, in animals and humans. Therefore, is important to understand physiological mechanisms and contributions of EVs in female reproduction in order to develop new tools to improve in vivo reproductive events and assisted reproductive techniques (ARTs). This review will provide the current knowledge related to EVs in female reproductive tissues and their role in ARTs.
Keywords: Extracellular vesicles; Female reproduction; Intercellular communication